Antiviral activity of an aqueous extract from the red alga Laurencia obtusa against influenza A and B viruses - Pérez-Riverol, Amilcar [UNESP]; Piñón Ramos, Alexander; Morier Díaz, Luis Francisco; Torres López, Yuneysi; Mendoza Llanes, Dianeya; del Barrio Alonso, Gloria (My University, 2014)
Introduction: antiviral therapy against infections caused by influenza viruses is based on the use of inhibitors of M2 protein and neuraminidase (NA). However, the emergence of seasonal strains resistant to both drug groups has led to the search for new anti-influenza medications. Extracts from algae may be used as a source of compounds, considering the diversity of metabolites described for these organisms. Objective: evaluate the in vitro antiviral activity of an aqueous extract from the red alga Laurencia obtusa against influenza A (H1N1), A (H3N2) and B viruses. Methods: cytotoxicity was evaluated in MDCK cells by cell viability estimation in the presence of growing concentrations of the extract. The effects over viral replication were quantified by determining hemagglutinin (HA) levels and inhibition of the cytopathic effect (CPE). The selective index (SI) was estimated by SI=CC50/CE50 Results: the aqueous extract of Laurencia obtusa showed in vitro antiviral activity against influenza B, A (H3N2) and A (H1N1) viruses with SI values of 7.73, 11.79 and 12.95, respectively. Conclusions: Laurencia obtusa inhibits the replication of influenza viruses, a fact of great clinical importance. Secondary assays to characterize the biological activity and molecular composition of the extract may lead to the development of novel antiviral compounds. The present paper is the first report on the inhibitory activity of this macroalga species against influenza viruses.
Actividad antiviral de un extracto acuoso del alga roja Laurencia obtusa frente a virus influenza A y B
Keywords: Algae; Antiviral; Influenza; Laurencia obtusa; Natural extracts